2016
DOI: 10.1371/journal.pone.0167235
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Non-Human Primate Model of Alpha-Synucleinopathy for Development of Therapeutics for Parkinson’s Disease: Optimization of AAV1/2 Delivery Parameters to Drive Sustained Expression of Alpha Synuclein and Dopaminergic Degeneration in Macaque

Abstract: Recent failures in clinical trials for disease modification in Parkinson’s disease have highlighted the need for a non-human primate model of the synucleinopathy underpinning dopaminergic neuron degeneration. The present study was defined to begin the development of such a model in cynomolgus macaque. We have validated surgical and vector parameters to define a means to provide a robust over-expression of alpha-synuclein which is associated with Lewy-like pathology and robust degeneration of the nigrostriatal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 24 publications
0
41
0
Order By: Relevance
“…This magnitude of increase has functional benefit, being associated with a complete absence of behavioral deficit in the cylinder test and no increase in striatal dopamine turnover, a change considered to be compensating for reduced dopaminergic transmission. In the macaque model of PD that was recently developed (Koprich et al, 2016), AAV1/2-hourA53T-aSyn vectors were injected bilaterally into the SN. Over 4-8 months, this model showed an increase in striatal hA53T-aSyn, a decrease in TH 1ve cells in the SN (by ∼40%), and decreases in striatal dopamine and DAT (by ∼50%).…”
Section: Discussionmentioning
confidence: 99%
“…This magnitude of increase has functional benefit, being associated with a complete absence of behavioral deficit in the cylinder test and no increase in striatal dopamine turnover, a change considered to be compensating for reduced dopaminergic transmission. In the macaque model of PD that was recently developed (Koprich et al, 2016), AAV1/2-hourA53T-aSyn vectors were injected bilaterally into the SN. Over 4-8 months, this model showed an increase in striatal hA53T-aSyn, a decrease in TH 1ve cells in the SN (by ∼40%), and decreases in striatal dopamine and DAT (by ∼50%).…”
Section: Discussionmentioning
confidence: 99%
“…The cynomolgus monkey (Macaca fascicularis) is one of the most studied non-human primates (NHP) in neuroscience and medicine (6,7). Recent advances in transgenesis and genome-editing technologies have led to successful development of 5 new cynomolgus monkey models to study genetic human neurological disorders (8)(9)(10), making this species an excellent experimental NHP model for brain researchers.…”
mentioning
confidence: 99%
“…They designed a rAAV1/2‐A53T ∝‐syn injected bilaterally in six cynomolgus macaques. ∝‐Synuclein was expressed in >85% of nigral neurons, the number of TH+ neurons decreased by 50%, and dopamine neurochemistry showed a 21%‐72% reduction according to the groups . Based on α‐syn delivery, these studies demonstrated the efficacy of this strategy to model PD.…”
Section: The Different Types Of Nhp Transgenic Modelsmentioning
confidence: 74%